Mechanistic Targets and Nutritionally Relevant Intervention Strategies to Break Obesity–Breast Cancer Links - Bustamante-Marin, Ximena M.; Merlino, Jenna L.; Devericks, Emily; Carson, Meredith S.; Hursting, Stephen D.; Stewart, Delisha A. (Frontiers in Endocrinology, 2021)
The worldwide prevalence of obesity and overweight status has tripled since 1975. More than 40% of adults and nearly 13% of the population were overweight and obese respectively in 2016; accounting for more than 70% of adults in the US alone. Obese individuals often display multiple metabolic perturbations, such as insulin resistance, immunosuppression, and persistent inflammation. These alterations in homeostatic mechanisms underlie the clinical parameters of metabolic syndrome, an established risk factor for many cancers, including breast cancer. Within the growth-promoting, proinflammatory milieu of the obese state, crosstalk between adipocytes, immune cells and breast epithelial cells occurs via obesity-associated hormones, cytokines, and other mediators that can enhance breast cancer risk and/or progression. This review synthesizes evidence on the biological mechanisms underlying the obesity-breast cancer link, with emphasis on hormone/growth factor signaling, inflammation and immunosuppression, and vascular integrity processes. These interrelated pathways represent possible mechanistic targets for disrupting the obesity-cancer link. Established and emerging mechanism-based interventions, especially in the context of nutrition, to reduce the burden of obesity on breast cancer will also be discussed.